If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 9(4) + -4x Multiply 9 * 4 2y = 36 + -4x Solving 2y = 36 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 18 + -2x Simplifying y = 18 + -2x
| 10x+15=2x+21 | | 8(u-8)=-5-38 | | t^2+3t-10=0 | | 2x+5=-40-7x | | x/2-(2x+1)/6=(x+1)/3 | | 8(u-8)=-5lu-38k | | x(21-2x)(39-2x)= | | -10z^2+11z=3 | | 5t-(t-2)=2-3.(t-5) | | 71-6x=39x+21 | | 13-8x=173-36x | | 5x^2+8=2x | | 7(t+4)+3(2t-5)= | | 19-y=x-x | | 7(q+2)=7q+14 | | 2x+4x=21 | | =8+8 | | 2x=62 | | x+2(y-x)=5+x | | 4x+27=191 | | 5r^2-39r-8=0 | | -15=-7y+4(y+3) | | 5(29-5x)=x-112 | | -2u+5=9-3u | | 2x+17=74 | | 3x-24+5x=7x+24 | | 12x+3y=y+9 | | 2(3y+4)=4-3 | | 0.5(4x-10)=x+15 | | 66-5x=31x+18 | | 6x+7.1=20.3 | | 2x+12=380 |